GAMBARAN SIKAP TENTANG MENOPAUSE PADA WANITA PREMENOPAUSE DI DESA LEDUG KECAMATAN KEMBARAN KABUPATEN BANYUMAS TAHUN 2014 - Tin Utami (Universitas Harapan Bangsa Purwokerto, 2014)
Sindarom menopause experienced by many women nearly all the world at the ageof 47-51 years of physical and psychological changes that affect demeanor.Interest to know the description of knowledge and attitudes about menopausepremenopausal women in the village Ledug Kembaran subdistrict, Banyumasregency of 2014.This research method is quantitative descriptive cross-sectional approach,instrument used was a questionnaire given to 83 respondents using purposivesampling technique that will be analyzed by univariate analysis.The results showed that attitudes about menopause in premenopausal women inthe village Ledug mostly in the category of positive attitude that as many as 47people (56.6%).It is concluded that the description of the attitude in women 47-51 years ofmenopause mostly have a positive attitude.Keywords: Menopause, Attitude.